The influence of brand image and digital marketing on the decisions to visit tourists to improve the community's economy in Sayum Sabah - Sekar Chalifah Segara; Ihsan Effendi; Adelina Lubis (Enrichment : Journal of Management, 2023)
This study aimed to determine the effect of Brand Image and Digital Marketing on the decision to visit tourists to improve the economy of the people in Sayum, Sabah. Sayum Sabah village is one of the Sibolangit sub-district villages with beautiful natural scenery and abundant agricultural produce. However, Sayum Sabah village is the poorest village in the Sibolangit area, requiring special attention from various parties to maximize its natural potential in order to improve the welfare of the village population. The sample in this study was 98 tourist visitors. Multiple linear regression and hypothesis testing are the analytical methods used. The results of the study show that brand image has a significant effect on visiting decisions. Digital Marketing influences the decision to visit tourists to improve the people's economy in Sayum, Sabah. Branding is one way that can be used to form an image or uniqueness of a destination to maintain the sustainability of a tourist village through a marketing system. They are branding a function as a differentiator or comparison between brands or products. These results illustrate that Digital Marketing is a determinant of increasing Visit Decisions.